Deep IV in law : appellate decisions and texts impact sentencing in trial courts - Huang, Zhe; Zhang, Xinyue; Wang, Ruofan; Chen, Daniel L. (Cambridge : Cambridge University Press, 2022)
Do US Circuit Courts' decisions on criminal appeals influence sentence lengths imposed by US District Courts? This Element explores the use of high-dimensional instrumental variables to estimate this causal relationship. Using judge characteristics as instruments, this Element implements two-stage models on court sentencing data for the years 1991 through 2013. This Element finds that Democratic, Jewish judges tend to favor criminal defendants, while Catholic judges tend to rule against them. This Element also finds from experiments that prosecutors backlash to Circuit Court rulings while District Court judges comply. Methodologically, this Element demonstrates the applicability of deep instrumental variables to legal data.
Title from publisher's bibliographic system (viewed on 02 Sep 2022).
Keywords: Appellate courts -- United States; Sentences (Criminal procedure) -- United States